DEPOSITION OF THALLIUM-BASED SUPERCONDUCTING THIN-FILMS BY A SIMPLE THERMAL EVAPORATION METHOD - Lai, H; Vernonparry, K; Chern, J; Grovenor, C (1991)
Superconducting Tl-Ca-Ba-Cu-O thin films less than 1 mu m thick have been prepared on Y-stabilized ZrO2 (100), MgO (100), and SrTiO3 (100) substrates using thermal evaporation and a two-step annealing process involving the growth of BaCuO2 films followed by ex situ crystallization and thalliation under thallium oxide vapours. The authors have been able to fabricate reasonably uniform films of the Tl2Ca 1Ba2Cu2Ox (2122) and Tl 2Ca2Ba2Cu3Ox (2223) superconducting phases, and have successfully reduced the density of impurity phases by controlling the stoichiometry and morphology of the precursor films and the thalliation conditions. In addition, a 150 mu m wide, and 1 cm long, track patterned in one of these films using standard photolithography techniques shows a Tc0 of 102 K, a Jc in excess of 104 A cm-2 at 90 K and a strong bolometric response when illuminated with an He-Ne 1 mW laser.